Application value of high-quality nursing combined with methylprednisolone in treatment of sudden deafness: methylprednisolone in treatment of deafness - Lv, Haixia; Zhang, Yufang (Progress in Nutrition, 2021)
Objective: Explore the application value of high-quality nursing combined with methylprednisolone in the treatment of sudden deafness. Methods: The patients who came to our hospital for treatment due to sudden deafness from January 2017 to December 2019 were selected as the research object, and were divided into a control group (n=65) and an observation group (n=65) according to the random number table method. The group used routine nursing intervention, and the observation group used high-quality nursing intervention combined with methylprednisolone intervention to compare the efficacy, negative emotions, quality of life, nursing satisfaction and PTA of the two groups. Results: The effective rate of the observation group was 90.77% higher than that of the control group of 76.92%, the difference was statistically significant (P 0.05), The SAS and SDS scores of both groups decreased, and the observation group was significantly lower than the control group, the difference was statistically significant (P